Iqbal’s ideas on science and the muslims - Abdul Razak, Mohd Abbas (2011)
Muslims were able to embellish their civilization with great achievements in the areas of science and technology. The Holy Qur‟an not only speaks about spirituality but also on science and the natural world. The message found in the Qur‟an was the driving force in encouraging the Muslims to go into science and research. Their zeal and zest to understand the hidden message of Allah the Almighty in the natural world made them learn from people of the earlier civilizations such as the Greeks, Persians and Indians. Adopt, adapt and assimilate or integrate was the approach used by Muslims in taking knowledge from others outside the religion. During their heydays, the Muslims were the pioneers in the many areas of knowledge and science that include mathematics, medicine, algebra, alchemy, philosophy, sociology, geography, etc. The great Muslim personalities and the centers established for learning during the peak of their civilization drew Europeans scholars to learn from them. In modern times, the European renaissance movement which started in the 14th century got the impetus from the culture of learning, doing research and exploration that was shown by the Muslim scholars of the Golden Age of Islam (750-1258). All the celebrated works of the Muslim scholars in science and research came to a halt after the fall of Baghdad in 1258 which triggered the demise of the Islamic empires. The decline of the empires and the internal conflicts within the Ummah made them lag behind other nations in the areas of science and technology. This research paper intends to explore the ideas of Allama Mohammed Iqbal (1873-1938) on science and what happened in the Islamic civilization that hindered their progress in science and research. Besides that, it also intends to explore the approach advocated by Iqbal towards science and how it can be used to make this world a better place for the Muslims and others as well.